Relation of preconception eating behaviours to dietary pattern trajectories and gestational weight gain from preconception to late pregnancy - Loh, Jason; Loy, See Ling; Appannah, Geeta; Colega, Marjorelee T.; Godfrey, Keith M.; Yap, Fabian; Chong, Yap Seng; Eriksson, Johan G.; Chan, Jerry K.Y.; Chan, Shiao-yng; Chong, Mary F.F.; Lai, Jun S. (Academic Press, 2024)
Studies examining preconception eating behaviours with longitudinal dietary patterns from preconception to late pregnancy as well as gestational weight gain (GWG) are limited. We derived dietary pattern trajectories from preconception to late-pregnancy, and related preconception eating behaviours to these trajectories and GWG. Preconception eating behaviours were assessed using the Three-Factor Eating Questionnaire measuring cognitive restraint (CR) – conscious restriction of food intake, emotional eating (EE) – overeating in response to negative emotions, and uncontrolled eating (UE) – overeating with a feeling of lack of control. Dietary intakes were measured at preconception, 20–21 and 34–36 weeks' gestation with food frequency questionnaires. Dietary patterns were determined using factor analysis, and trajectories derived using group-based trajectory modelling. Inadequate and excessive GWG were defined according to Institute of Medicine guidelines based on weights at preconception and the last antenatal visit (median: 38 weeks' gestation). Two dietary patterns were derived: ‘Fast Food, Fried Snacks and Desserts (FFD)’ and ‘Soup, Fish and Vegetables (SFV)’. Adherence trajectories from preconception to late-pregnancy were characterised as consistently high (“stable-high”) and low (“stable-low”). Women with higher UE scores had higher odds of being in the “stable-high” trajectory (n = 34) of the FFD pattern [Odds Ratio (OR): 1.25, 95% Confidence Interval (CI): 1.03, 1.51], compared to “stable-low” (n = 260). Percentages of women with inadequate, adequate or excessive GWG were 21.7% (n = 70), 25.8% (n = 83), and 52.5% (n = 169), respectively; women with higher EE scores had a higher likelihood of excessive GWG [Relative Risk Ratio (RRR): 1.35, 95% CI: 1.02, 1.80], but this association was attenuated after adjusting for preconception body mass index. Eating behaviour interventions to improve dietary patterns among pregnant women may need to start as early as preconception, incorporating strategies to manage UE.